PSYCHOLOGICAL STRUGGLES AND INTERNAL CONFLICTS IN SONS AND LOVERS, MRS DALLOWAY, AND A PORTRAIT OF THE ARTIST AS A YOUNG MAN - Islam, Rafiqul (UC Journal: ELT, Linguistics and Literature Journal, 2025)
A broader transformation took place in the literary fields, mostly in terms of the protagonists' internal conflicts and psychological issues in the 20th century, which can be clearly seen in the works of prominent writers like D. H. Lawrence, Virginia Woolf, and James Joyce. This research article explores the psychological issues and internal conflicts of the protagonists of Sons and Lovers, Mrs. Dalloway, and A Portrait of the Artist as a Young Man. The main characters of these novels suffer from extreme identity and existential crises. Employing Freudian and Lacanian psychoanalytic frameworks alongside modernist narrative techniques, the study elucidates how the subconscious mind and the human psyche are intricately rendered in the portrayal of the protagonists. The most prominent writers of this period, for instance, D. H. Lawrence, Virginia Woolf, and James Joyce, largely use fragmented narratives to draw out the inner turmoil and obsessive-compulsive symptoms of the main characters in their novels. Focusing on conjugal relations, love, emotion, passion, psychological conflict, class conflict, and middle-class sentiment of the people of this period with a qualitative discussion, the paper finds that the Industrial Revolution and scientific development functioned as catalysts to transform the human psychology of this period.